Evidence of Foam Sclerotherapy in the Treatment of Recurrent Varicose Veins - Peter, Jochen; Pourhassan, Siamak (Phlebologie, 2019)
Purpose Efficacy and safety of ultrasound-guided foam sclerotherapy (UGFS) for the treatment of primary venous disease is proven, but the main application field of UGFS remains the treatment of recurrent varicose veins (RVV). The aim of this study is to determine the extent to which this treatment indication is evidence-based.Methods In PubMed and other publicly accessible databases, literature was reviewed until June 2018 and checked for relevance. The focus was on results with regard to anatomical success as well as clinical success and perception by patients.Results Several observational studies comprised a subgroup of RVV patients, but systematic stratification for RVV patients were only rarely performed. In most of these studies including the few reports specifically investigating RVV patients anatomical success as the primary outcome measure revealed similar results compared to primary interventions and favourable results in patients with neovascularization. Data on clinical outcome and patient perception were inconclusive due to low study numbers and insufficient stratification. Complications in RVV patients were rare.Conclusion Although the advantages inherent to the UGFS principle provide a strong rationale that this method best meets the requirements of the specific RVV characteristics, concept and previous observations should be supported by more evidence. Systematic studies in RVV patients with sufficient sample size are required.
Keywords: foam sclerotherapy; recurrent varicose veins; varices